The Role of Suppressors of Cytokine Signalling in Human Neoplasms. (16th March 2014) - Sasi, Walid; Sharma, Anup K.; Mokbel, Kefah
Abstract : Suppressors of cytokine signalling 1–7 (SOCS1–7) and cytokine-inducible SH2-containing protein (CIS) are a group of intracellular proteins that are well known as JAK-STAT and several other signalling pathways negative feedback regulators. More recently several members have been identified as tumour suppressors and dysregulation of their biological roles in controlling cytokine and growth factor signalling may contribute to the development of many solid organ and haematological malignancies. This review explores their biological functions and their possible tumour suppressing role in human neoplasms.